2013
DOI: 10.1007/s00383-013-3339-z
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and outcomes of penetrating thoracic and abdominal trauma among children

Abstract: The incidences of penetrating abdominal and thoracic trauma did not differ significantly. Penetrating injuries may be successfully managed by conservative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Thoracic injuries secondary to penetrating trauma are uncommon representing 25% of penetrating trauma in pediatrics. Male patients were the predominating gender which is consistent with published studies [4,9,12,13]. Moreover, Stab wound secondary to knives was the predominating MOI in our region as shown in numerous studies from other regions [4,9,13,15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thoracic injuries secondary to penetrating trauma are uncommon representing 25% of penetrating trauma in pediatrics. Male patients were the predominating gender which is consistent with published studies [4,9,12,13]. Moreover, Stab wound secondary to knives was the predominating MOI in our region as shown in numerous studies from other regions [4,9,13,15].…”
Section: Discussionsupporting
confidence: 91%
“…Male patients were the predominating gender which is consistent with published studies [4,9,12,13]. Moreover, Stab wound secondary to knives was the predominating MOI in our region as shown in numerous studies from other regions [4,9,13,15]. In the contrary, Schecter S et al showed that gunshot injuries were the most common MOI in pediatrics [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5 The majority of the litera ture pertains to adult patients; however, CM has also been shown to be safe in children. 7 A 2012 Cochrane review 8 identified only 1 randomized controlled trial (RCT) 9 comparing operative to nonopera tive management for any type of abdominal trauma in hemodynamically asymptomatic patients. That 1996 RCT by Leppäniemi and Haapiainen 9 randomized 51 stable, asymptomatic patients without evisceration to either man datory laparotomy or observation.…”
mentioning
confidence: 99%
“…Prehospital evaluation and assessment can predict the outcome of trauma patients. 6 , 7 Patients typically arrive at our ED without prior notification. Most of them arrive by their own vehicles.…”
Section: Discussionmentioning
confidence: 99%